How Tax Compliance, Audit Quality, and Financial Reporting Quality on Corporate Financial Performance in Manufacturing Companies - Dwitayanti, Yevi; Armaini, Rosy (The Es Accounting And Finance, 2024)
Within the framework of Indonesian manufacturing enterprises, this study explores the intricate links between tax compliance, audit quality, financial reporting quality, and firm financial performance. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS), a sample of 175 firms was examined. The effect of these variables on financial performance was evaluated using correlation analysis, hypothesis testing, and descriptive statistics. The findings show a strong positive correlation between business financial performance, financial reporting quality, audit quality, and tax compliance. This study adds to the body of knowledge by providing complex insights specific to the Indonesian manufacturing industry. These insights can be used by investors, policy makers, regulators, and firm management to enhance decision-making procedures and promote sustainable financial practices in the sector.